STUDI EFEKTIVITAS DISTRIBUSI PUPUK BERSUBSIDI DAN DAMPAKNYA TERHADAP PENDAPATAN PETANI PADI SAWAH (ORYZA SATIVA L.) - Apriyani, Nina; Ayu Andayani, Sri; Umyati, Sri (Journal of Sustainable Agribusiness, 2025)
This study, entitled “A Study on the Effectiveness of Subsidized Fertilizer Distribution and Its Impact on the Income of Rice Farmers,” aims to analyze how the effectiveness of subsidized fertilizer distribution influences farmers' income. The research was conducted in Tolengas Village, Tomo Subdistrict, Sumedang Regency, with respondents selected using the Slovin formula at a 60% precision level. A descriptive-quantitative method was employed, utilizing the Income Effectiveness Distribution (IED) approach, farm business analysis, and simple regression analysis. The results show that the distribution of subsidized fertilizers in Tolengas Village was classified as effective and has a significant impact on rice farmers’ income, as indicated by a significance value of 0.013, which is lower than the threshold of 0.05. These findings highlight the importance of efficient and well-targeted fertilizer distribution, along with consistent technical support, in improving the welfare of rice farmers